Distance relaying algorithm for phasor measurement unit assisted zone-3 relays of series compensated wind integrated system - Prakash T.; Mohanty S.R.; Singh V.P. (My University, 2025)
The signals of wind integrated system are contaminated with inter-harmonic components which may result in erroneous calculations of apparent impedance seen by the distance relays. Therefore, it is indispensable to filter these signals before being used by relays. Presently, the measurements obtained from phasor measurement units (PMUs) are effectively used by distance relays for zone-3 protection. However, PMUs use discrete Fourier transform (DFT) algorithm to compute phasors which may produce incorrect results in presence of inter-harmonics. To overcome this issue, a matrix pencil method is proposed as a pre-processing filtering technique for PMU assisted distance relays. The analog input signals to PMUs are filtered by the matrix pencil algorithm to eliminate inter-harmonics present in the signals and the phasors are computed using DFT algorithm. These phasors are utilized by zone-3 distance relays to estimate the impedance trajectories. To test the effectiveness of proposed distance relaying algorithm, IEEE 14-bus system with a series compensated line is integrated with wind energy and is simulated under diverse test cases of different operating conditions. The impacts of fault resistances, type of faults and fault inception angles on the performance of proposed technique are examined and the results are compared with different signal processing techniques. © The Institution of Engineering and Technology 2019.